Does Financial Contagion Really Happen? - Devanto Shasta Pratomo, Rido Tanago, Munawar Ismail, Ghozali Maski, (Opción, 2020)
The purpose of this paper is to answer whether contagion happens during financial crises. This paper surveys the various definitions, measuring, and findings from financial contagion literature. We find that contagion or spillover happened slightly before and shortly during the global financial crisis even there is capital flow from the United States to some EMEs. In conclusion, there is still disagreement about the definition of contagion, whether it is a spillover or contagion, whether there is a negative or positive spillover, also which definition of contagion to be used; wide or narrow definition.